The governance capacities of Brexit from a Scottish perspective: The case of fisheries policy. (July 2022) - Connolly, John; Zwet, Arno van der; Huggins, Christopher; McAngus, Craig
Brexit leads to uncertainties about how policies will be 'rescaled' from the European Union back to the United Kingdom and its devolved governments. Interviews with key Scottish Government officials show how the UK's withdrawal from the Common Fisheries Policy presents mixed challenges for the Scottish policy system to absorb policy change at analytical, administrative, political, and communicative levels. Our analysis finds that absorbable areas concern fisheries management, operations, and analysis. Yet there are capacity areas that will require greater investment at political, communicative, and relational levels. This article makes an important contribution to research on the multi-level governance capacities for accommodating Brexit in UK policy-making. In doing so, our contribution applies the governance capacities literature to a new field of scholarship in relation to Brexit studies.